Minimally invasive gastrectomy and the risk of pancreas-related morbidity - Akateh, Clifford; Cloyd, Jordan M. (Laparoscopic Surgery, 2018)
For most of the last century, open gastrectomy (OG) has been the standard approach for gastric cancer. However, in recent years there has been growing acceptance of laparoscopic gastrectomy (LG), first performed by Kitano in 1994 (1), as an alternative and equally effective approach.